Variability in iodine in temperate seaweeds and iodine accumulation kinetics of Fucus vesiculosus and Laminaria digitata (Phaeophyceae, Ochrophyta). Issue 1 (15th December 2017) - Nitschke, Udo; Walsh, Philip; McDaid, Jade; Stengel, Dagmar B.
Abstract : The biogeochemistry of iodine in temperate coastal ecosystems is largely mediated by macroalgae, which act as a major biological sink and source of iodine. Their capacity to accumulate, retain and release iodine has been associated with abiotic and biotic stressors, but quantitative information is limited. We evaluated the seasonal iodine retention capacity of eleven macroalgal species belonging to different systematic groups, collected from two sites in Ireland. Iodine accumulation and retention were then further quantified in Fucus vesiculosus and Laminaria digitata in relation to I − concentrations in seawater and temperature. In general, iodine contents were ~10 1 –10 2  μmol · (g dw) −1 for Laminariales, 10 0 –10 1  μmol · (g dw) −1 for Fucales, 10 −1 –10 0  μmol · (g dw) −1 for Rhodophyta, and 10 −1  μmol · (g dw) −1 for Chlorophyta. Typically, algal iodine contents were above average in winter and below average in summer. Iodine accumulation in F. vesiculosus and L. digitata depended on I − availability and followed the Michaelis‐Menten kinetic. The ratio of maximum accumulation rate to half accumulation coefficient (ρmax : K t ) was 2.4 times higher for F. vesiculosus than for L. digitata, suggesting that F. vesiculosus was more efficient in iodine accumulation. Both species exhibited a temperature‐dependent net loss of iodine, and only an exposure to sufficient external I − concentrations compensated for this loss. This study revealed that both environmental (e.g., I − in seawater, temperature) and organismal (e.g., the status of the iodine storage pool) variables determine retention and variability in iodine in temperate seaweeds.